La0.1SrxCa0.9−xMnO3−δ-Sm0.2Ce0.8O1.9 composite material for novel low temperature solid oxide fuel cells. (6th July 2017) - Wang, Xunying; Afzal, Muhammad; Deng, Hui; Dong, Wenjing; Wang, Baoyuan; Mi, Youquan; Xu, Zhaoyun; Zhang, Wei; Feng, Chu; Wang, Zhaoqing; Wu, Yan; Zhu, Bin
Abstract: Lowering the operating temperature of the solid oxide fuel cells (SOFCs) is one of the world R&D tendencies. Exploring novel electrolytes possessing high ionic conductivity at low temperature becomes extremely important with the increasing demands of the energy conversion technologies. In this work, perovskite La0.1 Srx Ca0.9−x MnO3−δ (LSCM) materials were synthesized and composited with the ionic conductor Sm0.2 Ce0.8 O1.9 (SDC). The LSCM–SDC composite was sandwiched between two nickel foams coated with semiconductor Ni0.8 Co0.15 Al0.05 LiO2−δ (NCAL) to form the fuel cell device. The strontium content in the LSCM and the ratios of LSCM to SDC in the LSCM-SDC composite have significant effects on the electrical properties and fuel cell performances. The best performance has been achieved from LSCM-SDC composite with a weight ratio of 2:3. The fuel cells showed OCV over 1.0 V and excellent maximum output power density of 800 mW cm −2 at 550 °C. Device processes and ionic transport processes were also discussed. Highlights: Electrolyte layer is replaced by La0.1 Srx Ca0.9−x MnO3−δ -Sm0.2 Ce0.8 O1.9 composite. Investigate the influence of Sr content in the LSCM on the SOFC performances. Study the effect of the ratio between LSCM and SDC on the SOFC performances. The novel SOFCs showed OCV over 1.0 V. The Pmax is 800 mW cm −2 at 550 °C for the La0.1 Sr0.9 MnO3−δ :SDC with 2:3 ( w : w ).